2018
DOI: 10.1021/acsomega.8b01412
|View full text |Cite
|
Sign up to set email alerts
|

Electrosprayed Polymer-Hybridized Multidoped ZnO Mesoscopic Nanocrystals Yield Highly Efficient and Stable Perovskite Solar Cells

Abstract: Solid-state perovskite solar cells have been expeditiously developed since the past few years. However, there are a number of open questions and issues related to the perovskite devices, such as their long-term ambient stability and hysteresis in current density–voltage curves. We developed highly efficient and hysteresis-less perovskite devices by changing the frequently used TiO 2 mesoscopic layer with polymer-hybridized multidoped ZnO nanocrystals in a common n–i–p structure for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…Recent efforts have increased PCE for ZnO‐based PSC to over 20% by addressing these stability concerns by “passivating” the surface with magnesium oxide, ethanolamine, polyethylenimine, and ZnS . Despite these improvements however, the reactions of methylammonium cations at ZnO interfaces have remained unresolved, limiting the long‐term stability of ZnO–perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have increased PCE for ZnO‐based PSC to over 20% by addressing these stability concerns by “passivating” the surface with magnesium oxide, ethanolamine, polyethylenimine, and ZnS . Despite these improvements however, the reactions of methylammonium cations at ZnO interfaces have remained unresolved, limiting the long‐term stability of ZnO–perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Hydrogen is pacing up to lead the global race of energy requirement, with an increasing current demand of 70 Mt of H 2 /year. 4 − 6 Currently, emission-intensive processes predominantly used for hydrogen production are methane reforming (i.e., produces 7 kg CO 2 /kg H 2 ) and coal gasification (i.e., produces 18–20 kg CO 2 /kg H 2 ), which results in wasting a large amount of catalyst due to the growth of carbon over the catalyst surface. 7 − 11 In 2009, it was reported that about 150 000–170 000 tons of catalyst from hydroprocessing was deactivated or spent annually, with about an annual increase of 5%, which is predicted to be now in the range of 232 500–263 500 t/year.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many research efforts have been invested on improving the performance, efficiency and stability of different types of emerging photovoltaics (PVs) such as dye sensitized, [1][2][3][4][5][6][7][8][9][10] organic, [11][12][13][14][15][16][17][18][19][20][21][22] and perovskite PVs. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] While conventional silicon solar cells are heavy, fragile, and rigid, flexible solar cells represent a good alternative to the silicon counterparts, because of not only their flexibility, but also their lightweight, which enable their integration in portable electronic applications. Recently, scientists have carried out significant research and development efforts in order to improve the performance and the stability of flexible solar cells.…”
Section: Introductionmentioning
confidence: 99%